Microstructure is associated with motor outcomes following Deep Brain Stimulation in Parkinson’s disease - Philipp Alexander Loehrer; Julia Freigang; Miriam H. A. Bopp; Alexander Calvano; Haidar S. Dafsari; Julius Wichmann; Amelie Seidel; Carolin Aberle; Susanne Knake; Christopher Nimsky; Lars Timmermann; Marcus Belke; et al. (npj Parkinson's Disease)
Abstract Deep brain stimulation of the subthalamic nucleus (STN-DBS) is an established intervention for alleviating both motor and non-motor symptoms in advanced Parkinson’s disease (PD). However, patient outcomes may vary widely, underscoring the need for predictive biomarkers. Neuroimaging techniques, such as neurite orientation dispersion and density imaging (NODDI), a biophysical model-based MRI technique, offer promise in forecasting clinical outcomes and supporting preoperative counseling. This prospective, open-label study aimed to identify microstructural markers that correlate with short-term motor outcomes following STN-DBS in PD patients. Thirty-five patients underwent diffusion MRI and comprehensive clinical evaluations preoperatively and six months postoperatively. Evaluations were performed in the ON-medication as well as ON-medication/ON-stimulation state. A whole-brain voxel-wise analysis was conducted to explore associations between microstructural metrics and motor outcomes. Permutation-based statistical methods were applied to adjust for multiple comparisons. Intact microstructure in the bilateral putamen, bilateral insula, and left pallidum was significantly associated with a greater postoperative motor symptom improvement. Additionally, preserved microstructure in the pre- and postcentral gyrus and right precuneus was associated with increased duration with good mobility and without troublesome dyskinesia, and reduced time with poor mobility. These findings suggest that diffusion MRI may serve as valuable tool for identifying patients likely to exhibit favorable motor outcomes following STN-DBS. Incorporating microstructural data into preoperative counseling could enhance patient selection and optimize therapeutic strategies.